1965
DOI: 10.1037/h0022208
|View full text |Cite
|
Sign up to set email alerts
|

Vision in the Ganzfeld.

Abstract: The data show the experience of such fields to be characterized by reports of: immersion in a "sea of light" which separates into figure and ground as brightness is increased, chromatic adaptation in colored fields, loss of efficiency in detecting the presence and movement of inhomogeneities introduced into the field, disorientation of the observer, an increased and fluctuating state of accommodation, and the occasional joint occurrence of an apparent cessation of function of the visual mechanism and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(20 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…Similar findings were found in sensory and perceptual deprivation experiments (Zubek and Welch, 1963; Zakay and Lobel, 1983; Grassion, 1986). Similar effects are found in real life situation which resemble perceptual deprivation like in the case of snow-blindness which create a ganzfeld (Avant, 1965). It can be concluded that the need for meaningful information is a genuine need of the cognitive system which strives to gain the optimal amount of information (Merhabian, 1977).…”
Section: Psychological Timesupporting
confidence: 65%
“…Similar findings were found in sensory and perceptual deprivation experiments (Zubek and Welch, 1963; Zakay and Lobel, 1983; Grassion, 1986). Similar effects are found in real life situation which resemble perceptual deprivation like in the case of snow-blindness which create a ganzfeld (Avant, 1965). It can be concluded that the need for meaningful information is a genuine need of the cognitive system which strives to gain the optimal amount of information (Merhabian, 1977).…”
Section: Psychological Timesupporting
confidence: 65%
“…When a subject stares at an empty field with homogeneous coloring (no brightness gradients and contours in it) for a long time, sooner or later an experience of “fading out” or “emptiness” of the visual sense occurs (Avant, 1965; Wackermann et al, 2008). Colorful visual experience disappears.…”
Section: Empirical Facts Consistent With C = L × Dmentioning
confidence: 99%
“…It is well known that a Ganzfeld distorts many visual functions (12), impairs target detection (13), and degrades other processes which are considered to be basically foveal, such as reading (14). We therefore tested the hypothesis that loss in the water of much of the usual peripheral stimulation is the cause of the drop in stereoacuity.…”
Section: Visual Acuitymentioning
confidence: 99%